2019
DOI: 10.1016/j.contraception.2019.07.146
|View full text |Cite
|
Sign up to set email alerts
|

The contraceptive and reproductive history and planning goals of trans-masculine adults: a mixed-methods study

Abstract: Objectives: This study aims to identify factors associated with the reproductive planning of transmasculine adults. Study design: Between 2015 and 2016, providers enrolled 150 trans-masculine adults in a sexual health study assessing sociodemographics, social support, gender affirmation, sexual partnering, and reproductive history and planning. A brief clinical interview assessed contraceptive use and concerns. Bivariate and multivariable logistic regression analyses examined associations between participant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 12 publications
2
15
0
1
Order By: Relevance
“…The few published empirical studies investigating this topic have largely focused on ascertaining the prevalence of contraceptive use among transmasculine adults. 3,10,12,13 For example, in a medical chart review of 26 transgender men, Cipres and colleagues found that most reported using condoms (38%) or no contraceptive method (42%). 3 An online survey of 197 transgender men by Light et al found that 60% reported using contraceptives, especially condoms (49%) and the pill (34%).…”
Section: Contraceptive Beliefs Decision Making and Care Experiences mentioning
confidence: 99%
See 4 more Smart Citations
“…The few published empirical studies investigating this topic have largely focused on ascertaining the prevalence of contraceptive use among transmasculine adults. 3,10,12,13 For example, in a medical chart review of 26 transgender men, Cipres and colleagues found that most reported using condoms (38%) or no contraceptive method (42%). 3 An online survey of 197 transgender men by Light et al found that 60% reported using contraceptives, especially condoms (49%) and the pill (34%).…”
Section: Contraceptive Beliefs Decision Making and Care Experiences mentioning
confidence: 99%
“…10 And in a study of 150 transmasculine adults, Stark et al found that 37% were currently using a method, including condoms (24%), IUDs (8%) and the pill (3%). 12 Even fewer studies examined the specific and unique aspects of contraceptive use within the transmasculine population, including gender affirmation, lack of provider competency in transgender reproductive health care and gender discrimination in reproductive health care settings. [12][13][14] Understanding the patient-, provider-and system-level conditions that shape transmasculine individuals' contraceptive use is essential for developing tailored educational materials, programs and practices to facilitate high-quality contraceptive care among this marginalized and underserved population.…”
Section: Contraceptive Beliefs Decision Making and Care Experiences mentioning
confidence: 99%
See 3 more Smart Citations